A REVIEW OF GROWTH STAGE DEFICIT IRRIGATION AFFECTING STICKY MAIZE PRODUCTION - Bui, Ha Manh (GeoScience Engineering, 2017)
The shortage of water resource influences the future sustainability of sticky Maize (Zea mays L.) production. Deficit irrigation (DI) – a water management strategy- has gained high attention from scientist because of enhanced water use efficiency (WUE). Nonetheless, in reality, when applying this technique, its impact on yield and economic returns should be considered. Through an analytical literature review, this study exam the effect of DI grow state on Maize production factor i.e. yield, WUE, and economic returns. The results revealed that Maize’s WUE could be upgraded with lowest reduction in yield as water stress is imposed during the vegetative or maturation growth stages. Therefore, the profitable returns could be reached even as the yield is reduced; however, the economic return is sensitive to commodity prices. The present review addresses the Maize flexible capacities on growth stage water stress presents an opportunity for optimization of irrigated water and profit preservation by accurately judging managing time of irrigation implementation.